Omitted Speech and Literary Speech in Río Escondido: Some Visual and Literary Keys That Dilute or Clarify the Authorship of a Script - Méndez López, Nancy Fabiola; Arranz Mínguez, Conrado J. (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The main objective of this work is to understand the contribution of the script to the film Río Escondido in the creation of a collective, polyphonic, convergence work, and far away from a classic vision of authorship. We propose a documentary analysis of the story and another of the script as a semiotic vehicle that enables going from a written language to a visual one. This last analysis focuses on the relevance of the literary discourse of the script that is omitted from the film. This one can create a discord between the scriptwriter and the director. Finding these fissures enables an approach to new ways of seeing Mexican cinema, away from industry and clichés, and closer to the literary field.